Simple signals indicate which period of the annual cycle drives declines in seasonal populations. (20th October 2019) - Burant, Joseph B.; Betini, Gustavo S.; Norris, D. Ryan
Abstract: For declining wild populations, a critical aspect of effective conservation is understanding when and where the causes of decline occur. The primary drivers of decline in migratory and seasonal populations can often be attributed to a specific period of the year. However, generic, broadly applicable indicators of these season‐specific drivers of population decline remain elusive. We used a multi‐generation experiment to investigate whether habitat loss in either the breeding or non‐breeding period generated distinct signatures of population decline. When breeding habitat was reduced, population size remained relatively stable for several generations, before declining precipitously. When non‐breeding habitat was reduced, between‐season variation in population counts increased relative to control populations, and non‐breeding population size declined steadily. Changes in seasonal vital rates and other indicators were predicted by the season in which habitat loss treatment occurred. Per capita reproductive output increased when non‐breeding habitat was reduced and decreased with breeding habitat reduction, whereas per capita non‐breeding survival showed the opposite trends. Our results reveal how simple signals inherent in counts and demographics of declining populations can indicate which period of the annual cycle is driving declines.